2015
DOI: 10.1146/annurev-clinpsy-032814-112753
|View full text |Cite
|
Sign up to set email alerts
|

fMRI Functional Connectivity Applied to Adolescent Neurodevelopment

Abstract: The exponential rise in the number of functional brain connectivity studies, particularly those examining intrinsic functional connectivity (iFC) at rest, and the promises of this work for unraveling the ontogeny of functional neural systems motivate this review. Shortly before this explosion in functional connectivity research, developmental neuroscientists had proposed theories based on neural systems models to explain behavioral changes, particularly in adolescence. The current review presents recent advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 95 publications
(112 reference statements)
4
70
0
Order By: Relevance
“…Building on this technique, examining task-based functional connectivity may be an important step towards understanding local changes in brain activity during performance of a task by exploring the neural network in which information is shared and integrated in response to different cognitive processes (Ernst, Torrisi, Balderston, Grillon, & Hale, 2015). This study explored the brain’s functional organization associated with SWM using four seeds within the fronto-parietal network: bilateral DLFPC and bilateral PPC.…”
Section: Discussionmentioning
confidence: 99%
“…Building on this technique, examining task-based functional connectivity may be an important step towards understanding local changes in brain activity during performance of a task by exploring the neural network in which information is shared and integrated in response to different cognitive processes (Ernst, Torrisi, Balderston, Grillon, & Hale, 2015). This study explored the brain’s functional organization associated with SWM using four seeds within the fronto-parietal network: bilateral DLFPC and bilateral PPC.…”
Section: Discussionmentioning
confidence: 99%
“…At the network level, changes in the intrinsic functional connectivity across development have been reported (see review, Ernst et al (2015)). A recent resting state fMRI study revealed that the intrinsic functional connectivity increased between the dorsal caudate nucleus and posterior cingulate cortex from childhood into adulthood.…”
Section: Striatum and Its Networkmentioning
confidence: 99%
“…Temporal coherence in spontaneous low-frequency signal fluctuations at rest is hypothesized to reflect a history of co-activation suggesting a functional relationship between regions (Ernst et al, 2015). Several statistical methods have been applied to fcMRI data, including seed-based approaches, (e.g., psychophysiologic interaction), graph analysis techniques on region-to-region connectivity, and independent/principal component analysis (Power et al, 2010), which vary in the degree to which they are hypothesis- or data-driven (Ernst et al, 2015). Seed-based approaches select a small number of regions a priori and assess correlations between fluctuations the signal in these regions and fluctuations in voxels throughout the rest of the brain.…”
Section: Structural and Functional Connectivity Of The Accmentioning
confidence: 99%
“…Overall, a transition from local to distributed connectivity takes place, whereby children show greater resting-state connectivity between local regions and adults display a more distributed pattern of long-range connectivity throughout the brain (Power et al, 2010). Furthermore, several distinct neural networks strengthen their connectivity while others weaken across development (Ernst et al, 2015). …”
Section: Typical Development Of Functional Acc Connectivity: Reviewmentioning
confidence: 99%